A stepped-wedge implementation and evaluation of the healthy active peaceful playgrounds for youth (HAPPY) intervention - Dean Dudley; Wayne Cotton; Louisa Peralta; Matthew Winslade (BMC, 2018)
Abstract Background Increasing physical activity in children is a health priority. The Healthy Active Peaceful Playgrounds for Youth (HAPPY) study aimed to examine a multi-component playground intervention designed to increase the proportion of physical activity during recess and lunch of primary school students. Methods The 2016 Australian focused HAPPY Study was a 12-month, metropolitan primary school based intervention, which was evaluated using a stepped wedge design. The intervention combined teacher development, environmental modifications, and peer support, with the outcomes of increasing physical activity, and analysing students' sources of social support to be physically active. Results Between baseline and follow-up, the proportion of students involved in vigorous activities during recess and lunch times increased significantly from 15 to 25% (p < 0.001). No differences were recorded in sources of social support. Conclusions The HAPPY project demonstrated an increase in the proportion of physical activity intensity during recess and lunch times in primary schools, although further investigation is required to determine what components of the study had the greatest effect. Trial registration This study was retrospectively registered with the Australian and New Zealand Clinical Trials Registry ACTRN12616000575437. Date of registration: 4 May 2016.